Immunity, tolerance and autoimmunity in the liver: A comprehensive review. (January 2016) - Doherty, Derek G.
Abstract: The hepatic immune system is constantly exposed to a massive load of harmless dietary and commensal antigens, to which it must remain tolerant. Immune tolerance in the liver is mediated by a number of specialized antigen-presenting cells, including dendritic cells, Kupffer cells, liver sinusoidal endothelial cells and hepatic stellate cells. These cells are capable of presenting antigens to T cells leading to T cell apoptosis, anergy, or differentiation into regulatory T cells. However, the hepatic immune system must also be able to respond to pathogens and tumours and therefore must be equipped with mechanisms to override immune tolerance. The liver is a site of accumulation of a number of innate lymphocyte populations, including natural killer cells, CD56 + T cells, natural killer T cells, γδ T cells, and mucosal-associated invariant T cells. Innate lymphocytes recognize conserved metabolites derived from microorganisms and host cells and respond by killing target cells or promoting the differentiation and/or activation of other cells of the immune system. Innate lymphocytes can promote the maturation of antigen-presenting cells from their precursors and thereby contribute to the generation of immunogenic T cell responses. These cells may be responsible for overriding hepatic immune tolerance to autoantigens, resulting in the induction and maintenance of autoreactive T cells that mediate liver injury causing autoimmune liver disease. Some innate lymphocyte populations can also directly mediate liver injury by killing hepatocytes or bile duct cells in murine models of hepatitis, whilst other populations may protect against liver disease. It is likely that innate lymphocyte populations can promote or protect against autoimmune liver disease in humans and that these cells can be targeted therapeutically. Here I review the cellular mechanisms by which hepatic antigen-presenting cells and innate lymphocytes control the balance between immunity, tolerance and autoimmunity in the liver. Highlights: Immune tolerance in the liver is mediated by a number of liver-resident antigen-presenting cells. The liver contains innate lymphocyte populations that can promote antigen presentation and stimulate T cell responses. Hepatic innate lymphocytes may promote or protect against autoimmune liver disease in humans.